Near‐Infrared Croconaine Rotaxanes and Doped Nanoparticles for Enhanced Aqueous Photothermal Heating. Issue 39 (21st August 2014) - Spence, Graeme T.; Lo, Shun Shang; Ke, Chenfeng; Destecroix, Harry; Davis, Anthony P.; Hartland, Gregory V.; Smith, Bradley D.
Abstract The photothermal effect is the generation of heat by molecules or particles upon high‐energy laser irradiation, and near‐infrared absorbers such as gold nanoparticles and organic dyes have a range of potential photothermal applications. The favourable photothermal properties of thiophene‐functionalised croconaine dyes were recently discovered. The synthesis and properties of novel croconaine rotaxane and pseudorotaxane architectures capable of efficient photothermal performance in both organic and aqueous environments are reported. The versatility of this dye‐encapsulation strategy was demonstrated by the preparation of two organic croconaine rotaxanes using different synthetic methods: the formation of an aqueous pseudorotaxane association complex, and the synthesis of water‐soluble, croconaine‐doped silicated micelle nanoparticles. All of these near‐infrared‐absorbing systems exhibit excellent photothermal behaviour, with pseudorotaxane and rotaxane formation vital for effective aqueous heat generation. Dye encapsulation provides steric protection to enhance the stability of a water‐sensitive croconaine dye, while rotaxane‐doped nanoparticles avoid detrimental band broadening caused by chromophore coupling.